2023
DOI: 10.1002/mp.16537
|View full text |Cite
|
Sign up to set email alerts
|

Incremental retraining, clinical implementation, and acceptance rate of deep learning auto‐segmentation for male pelvis in a multiuser environment

Abstract: Background Deep learning auto‐segmentation (DLAS) models have been adopted in the clinic; however, they suffer from performance deterioration owing to the clinical practice variability. Some commercial DLAS software provide an incremental retraining function that enables users to train a custom model using their institutional data to account for clinical practice variability. Purpose This study was performed to evaluate and implement the commercial DLAS software with the incremental retraining function for def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…It is highly possible that the contour labels from different ROs may vary due to their distinct training backgrounds, experiences, personal preferences, and other factors. 26,27 The inherent bias in human labels, on the other hand, can partially affect the selection of z values, which determine the pass criteria. When multiple ROs collaborate to define acceptability, some regions of the contour may demonstrate larger tolerances, with the acceptable deviation increasing to accommodate the varying perspectives of the ROs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is highly possible that the contour labels from different ROs may vary due to their distinct training backgrounds, experiences, personal preferences, and other factors. 26,27 The inherent bias in human labels, on the other hand, can partially affect the selection of z values, which determine the pass criteria. When multiple ROs collaborate to define acceptability, some regions of the contour may demonstrate larger tolerances, with the acceptable deviation increasing to accommodate the varying perspectives of the ROs.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of human subjectivity on the CSED system still remains uncertain even though a recent study revealed that bias in the labeling process can be mitigated by comparing the labels from multiple experts. 26 Future studies will be conducted by gathering different ROs' judgments on the same dataset and evaluating the effect of human bias in the proposed model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations